1997
DOI: 10.1002/(sici)1096-9861(19970428)381:1<81::aid-cne7>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Vagal preganglionic projections to the enteric nervous system characterized withPhaseolus vulgaris-leucoagglutinin

Abstract: The patterns and extent of vagal preganglionic divergence and convergence within the gastrointestinal tract of the rat were characterized with the anterograde tracer Phaseolus vulgaris-leucoagglutinin (PHA-L). Three weeks after tracer was iontophoretically injected into two to four sites within the dorsal motor nucleus of the vagus, wholemounts of perfused gut organs (stomach, duodenum, cecum) were prepared, counterstained with Cuprolinic blue, and processed for PHA-L using the avidin biotin complex with diami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 25 publications
9
69
0
Order By: Relevance
“…Previous observations have suggested that most, if not all, myenteric neurons in the stomach are contacted by vagal preganglionic terminals Holst et al, 1997), and the present results corroborate the conclusion. In addition, though, the present results for the first time indicate that virtually all of these efferent axonal projections are positive for alpha-synuclein.…”
Section: Alpha-synuclein-positive Pathways Innervating the Gutsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous observations have suggested that most, if not all, myenteric neurons in the stomach are contacted by vagal preganglionic terminals Holst et al, 1997), and the present results corroborate the conclusion. In addition, though, the present results for the first time indicate that virtually all of these efferent axonal projections are positive for alpha-synuclein.…”
Section: Alpha-synuclein-positive Pathways Innervating the Gutsupporting
confidence: 92%
“…Thus the Braak model suggests the general proposal that Parkinson's disease may be produced by an environmental pathogen that breaches the mucosal barrier of the gastrointestinal (GI) tract (and presumably the olfactory system as well; Hawkes et al, 2007) in susceptible individuals. Further, the model suggests that the stomach is the most likely starting point for any pathological insult to gain access to axons from the dorsal vagal complex, because of the heavy innervation of the GI tract by vagal preganglionics Holst et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Second, the Fos expression was induced in the enteric plexuses of the stomach and duodenum but not in the jejunum, ileum, and colon, a fact that accords with the denser distribution of the vagal innervation in the upper GI tract (52). Anterograde tracing studies showed that vagal efferent terminals form a dense network encircling or making putative contact with nearly all myenteric neurons in the rat corpus and antrum (19). The profuse, widespread, and similar magnitude of Fos expression in the corpus, antral, and duodenal myenteric ganglia in response to insulin hypoglycemia is consistent with the vagal efferent innervation in these areas (19).…”
Section: Discussionmentioning
confidence: 79%
“…This caudal raphe-DVC pathway plays an important role in vagalmediated stimulation of gastric functions by cold stress (6,70,71). Peripherally, the gastric and duodenal enteric plexuses, which innervate smooth muscle/mucosal layers and play important roles in regulating gastric and duodenal secretion and motility (14, 50), receive a dense and intricate network of vagal efferent axons (2,19,77). Studies on the neuronal responses to abnormal blood glucose levels in these central vagal-…”
mentioning
confidence: 99%
“…By the use of immunoelectron microscopy, nerve fibers and varicosities immunoreactive for either vAChT or NOS were found within the circular and longitudinal muscle layers. It is likely that the majority of these fibers were nerve terminals of enteric motor neurons, and it is unlikely that vAChT immunoreactivity was caused by vagal efferent fibers because these neurons do not terminate within the muscle layers (Holst et al, 1997). vAChT immunoreactivity was associated with either the membranes or within the lumen of vesicles within varicosities.…”
Section: Morphological Relationships Between Enteric Motor Neurons Anmentioning
confidence: 99%